Waiting for a visa - Ambedkar, B. R. (New Delhi Samyak Prakashan, 2018)
Here are some of the reminiscences drawn by Dr. Ambedkar in his own handwriting. The MSS traced in the collection of the people's education society were published by the society as a booklet on 19th March, 1990.
Keywords: Dalits-Social conditions; Social conditions; Autobiography